Evaluation of dry matter production and yield in early-sown wheat using near-isogenic lines for the vernalization locus Vrn-D1. (3rd April 2019) - Sawada, Hiroko; Matsuyama, Hiromi; Matsunaka, Hitoshi; Fujita, Masaya; Okamura, Natsumi; Seki, Masako; Kojima, Hisayo; Kiribuchi-Otobe, Chikako; Takayama, Toshiyuki; Oda, Shunsuke; Nakamura, Kazuhiro; Sakai, Tetsufumi; et al.
ABSTRACT: Wheat ( Triticum aestivum L.) grain yield is predicted to decrease in the future because of an increase in air temperature globally. To clarify the effects of the vernalization response gene in wheat to warmer winters, we compared dry matter production and grain yield between spring wheat 'Asakazekomugi' and its winter-type near-isogenic line (NIL) carrying different alleles of the vernalization response gene Vrn-D1 under early-, standard-, and late-sowing conditions. Under early-sowing conditions, dry matter production of the NIL carrying the winter allele of Vrn-D1, named Asa (Vrn-D1b), exceeded that of 'Asakazekomugi' from mid-March (after stem elongation in Asa (Vrn-D1b)) when the temperatures rose. Tiller number and leaf area index under early-sowing conditions were consistently higher in Asa (Vrn-D1b) than in 'Asakazekomugi' from mid-March onward. It was suggested that the early-sown 'Asakazekomugi' could not effectively absorb solar radiation to produce dry matter because of the acceleration of stem elongation caused by the Vrn-D1 gene during the cold season. The grain yield of Asa (Vrn-D1b) with early sowing was higher than with standard sowing. In contrast, the grain yield of 'Asakazekomugi' was lower in the early-sown crop than in the crop sown at the standard date. These results suggested that the higher grain yield of Asa (Vrn-D1b) than that of 'Asakazekomugi' under early-sown conditions could be due to Asa (Vrn-D1b) maintaining high dry matter production after the jointing stage by suppressing acceleration of growth caused by warm conditions after sowing. Abbreviations: CGR: crop growth rate; HI: harvest index; LAI: leaf area index; NIL: near-isogenic line; SNP: single-nucleotide polymorphism